1983
DOI: 10.1093/infdis/148.4.682
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Purified Human Plasma Prekallikrein Triggered by Cell Wall Fractions of Escherichia coli and Staphylococcus aureus

Abstract: Whether Escherichia coli and Staphylococcus aureus cell wall fractions can trigger the activation of prekallikrein was investigated in a mixture of purified human factor XII, prekallikrein, and high-relative-molecular-weight (Mr) kininogen. After exposure for 30 min to bacterial preparations (0.02-5 mg/ml) at 0 C, lallikrein amidolytic activity was expressed as a percentage of the optimal activation of prekallikrein induced by dextran sulfate. Lipopolysaccharide (LPS) fractions of five E coli strains and lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…29 contact pathway participates in host responses to pathogens. Consistent with this concept, several microbial activators of the contact pathway have been identified, including bacterial surface proteins, 68,69 lipopolysaccharide, 70 teichoic/lipoteichoic acid, 70 and, as discussed here, long-chain polyP. 5,27 The first reported role for polyP in blood clotting was a 2006 study from our laboratory that showed that polyP is strongly procoagulant, triggering clotting of plasma via the contact pathway as well as modulating downstream clotting reactions (see, in particular, step 1 in Figure 2A).…”
Section: Polyp In Plateletsmentioning
confidence: 71%
“…29 contact pathway participates in host responses to pathogens. Consistent with this concept, several microbial activators of the contact pathway have been identified, including bacterial surface proteins, 68,69 lipopolysaccharide, 70 teichoic/lipoteichoic acid, 70 and, as discussed here, long-chain polyP. 5,27 The first reported role for polyP in blood clotting was a 2006 study from our laboratory that showed that polyP is strongly procoagulant, triggering clotting of plasma via the contact pathway as well as modulating downstream clotting reactions (see, in particular, step 1 in Figure 2A).…”
Section: Polyp In Plateletsmentioning
confidence: 71%
“…Cell wall components of Gram-negative bacteria (e.g., endotoxin) and Gram-positive bacteria (e.g. peptidoglycan) can activate both the complement system and the contact system of intrinsic coagulation (2,3). Considerable evidence has accumulated that excessive activation of these cascade systems, with release of biologically active peptides (anaphylatoxines and bradykinin), plays a role in the pathophysiology of sepsis, notably Receivedfor publication 7 July 1988 and in revisedform 24 February 1989. when complicated by shock and/or adult respiratory distress syndrome (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the aprotinin plasma levels in our experiments exceeded 468 KIU/mL (10 ^mol/L) and should therefore have blocked relevant amounts of plasma kallikrein in the circulation. 2 ' 28 This notion is supported by a previous study in which high amounts of plasma kallikrein, rapidly generated in an in vivo model of dextran sulfate-induced activation of the contact phase of coagulation, were completely blocked at an aprotinin concentration of 400 KIU/mL. 29 Since the extent of kininogen cleavage was not influenced by administration of aprotinin, the question arises why aprotinin then attenuated arterial hypotension.…”
mentioning
confidence: 85%
“…1,2 Arterial hypotension is induced by LPS in many species of experimental animals. Both the contact and the complement systems have been found to be activated in patients with septic shock.…”
mentioning
confidence: 99%